Panic disorder aging characteristics: The role of telomerase reverse transcriptase gene and brain function - Ding, Huachen; Zhong, Yuan; Liu, Na; Wu, Huiqin; Xu, Huazhen; Wu, Yun; Liu, Gang; Yuan, Shiting; Zhou, Qigang; Wang, Chun (Frontiers in Aging Neuroscience, 2022)
Background: The memory decline and social function impairment are considered to be one of Panic disorder (PD) aging characteristics. The mechanism of the telomerase reverse transcriptase gene (TERT) of PD aging characteristics could be explored by imitated animal fear memory mode and case-control trial in humans. Methods: Promoter methylation within the gene encoding for TERT was measured in PD (n=32), and eligible Healthy controls (n=22). Cytosine-phosphate-guanine (CpG) regions and sites for analysis were used to the relationship with clinical characteristics, Regional homogeneity (ReHo). There were 15 Tert−/− mice and 21 normal mice for a contextual recent fear memory acquisition. Results: We reported that a significantly decreased level of methylation of human TERT (hTERT)gene was detected in PD patients compared with healthy controls and associated with the clinical characteristics of panic disorder, including social function damage and panic symptom severity. Regional homogeneity analysis showed that methylation of cg1295648 correlated with social function impairment through moderating the function of the left postcentral gyrus (PCG). The loss of TERT attenuated the acquisition of recent fear memory during contextual fear conditioning in mice. Conclusion: This study suggests that the TERT gene may play an important role in the pathogeny of PD aging characteristics. It is indicated that the hTERT gene methylation may become a biological marker for evaluating PD aging characteristics. These findings could potentially help us develop novel ways to prognose the outcome of panic disorder and enrich the research field of telomere genetic imaging in PD.